(untitled) (Research, Society and Development, 2022)
Forensic chemistry is an interdisciplinary area that provides valuable information to assist justice in solving criminal matters. Chemiluminescence is one of the most widely used methods for detecting bloodstains. Even after washing the crime scene, this technique is still able to identify the presence of biological material. In this context, the main objective for the development of this work is to review the main chemiluminescence techniques used in crime scenes. Among the most common techniques in chemiluminescence, those based on Luminol, Fluorescein, Bluestar Forensics and Lumiscene stand out as the most effective methods for detecting blood on different types of surfaces and even in washed scenarios. From the literature review, it was found that more research is needed to better understand the reaction mechanism involved in the usual materials in forensic sciences. In addition, the development of new materials with greater luminescence, greater contrasts, low toxicity, longer response time and high sensitivity.